Search for Neutrino Doublets and Triplets Using 11.4 yr of IceCube Data - R. Abbasi; M. Ackermann; J. Adams; S. K. Agarwalla; J. A. Aguilar; M. Ahlers; J.M. Alameddine; N. M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (The Astrophysical Journal)
We report a search for high-energy astrophysical neutrino multiplets, detections of multiple neutrino clusters in the same direction within 30 days, based on an analysis of 11.4 yr of IceCube data. A new search method optimized for transient neutrino emission with a monthly timescale is employed, providing a higher sensitivity to neutrino fluxes. This result is sensitive to neutrino transient emission, reaching per-flavor flux of approximately $1{0}^{-10}\,erg\,{cm}^{-2}\,{{\rm{s}}}^{-1}$ from the Northern Sky in the energy range E ≳ 50 TeV. The number of doublets and triplets identified in this search is compatible with the atmospheric background hypothesis, which leads us to set limits on the nature of neutrino transient sources with emission timescales of one month.